Pengaruh Media Sosial terhadap Pola Komunikasi Remaja - Yuniarta Permatahati Widyanti; Nasywa Natasya Az Zahra; Nita Vitriana; Soraya Rahmadhani; Mada Aditia Wardhana (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to systematically review the literature that discusses the influence of social media on adolescent communication patterns, especially in the context of organizational learning. Social media as part of the digital transformation has changed the way adolescents interact, not only in social aspects but also in informal learning processes. Through a Systematic Literature Review approach, this study maps key concepts, identifies research gaps, and explores future research directions. The results of the study indicate that social media plays an important role in shaping interpersonal communication, digital ethics, and adolescent self-identity. However, most previous studies are still geographically limited, descriptive, and have not linked social media use to organizational learning comprehensively. Therefore, it is necessary to develop an integrative theoretical model and longitudinal studies that consider the cultural, psychological, and social contexts of adolescents in the digital era.